2015
DOI: 10.3390/en8021291
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ground Fault Non-Directional Selective Protection Method for Ungrounded Distribution Networks

Abstract: This paper presents a new selective and non-directional protection method to detect ground faults in neutral isolated power systems. The new proposed method is based on the comparison of the rms value of the residual current of all the lines connected to a bus, and it is able to determine the line with ground defect. Additionally, this method can be used for the protection of secondary substation. This protection method avoids the unwanted trips produced by wrong settings or wiring errors, which sometimes occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Developed protection algorithm is compared with other earth fault algorithms in Table 3. Comparison is based on the methodology presented in [71]. Developed solutions are compared with conventional earth fault protection methods-residual voltage and ground fault directional current.…”
Section: Protection Algorithmmentioning
confidence: 99%
“…Developed protection algorithm is compared with other earth fault algorithms in Table 3. Comparison is based on the methodology presented in [71]. Developed solutions are compared with conventional earth fault protection methods-residual voltage and ground fault directional current.…”
Section: Protection Algorithmmentioning
confidence: 99%
“…Each DG is a 1-MVA synchronous generator. Nodes 4,5,6,10,11,12,13,and 15 are key nodes with VTs installed.…”
Section: The Ieee 30-node Meshed Distribution Systemmentioning
confidence: 99%
“…And the stability problems and large ground current caused by increasing penetration of DGs should also be paid attention . In Ou and other literature, it has been shown that the fault analysis method should consider the effect of unbalanced system configuration especially in neutral‐ungrounded system. This paper studies the urban distribution systems which is mainly cable based; thus, the conventional symmetrical fault analysis method is still valid in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…To detect an insulation fault, especially a line-to-earth fault, which potentially introduces an electric shock hazard or fire hazard, a suitable protective device of a proper sensitivity level should be selected and applied. The type of protective device and its operational algorithm depends on the type of power network (grounded, ungrounded, overhead line, cable line) [4,5], the necessity of detection of an arc fault [6,7], distorted voltages [8], special signals [9], DC currents [10,11], and the necessity of detection of non-sinusoidal alternating earth fault currents. Special attention should be given to the currents comprising very-low-frequency components [12] or high-order harmonics [13][14][15][16][17][18][19], as in circuits with power electronics converters [20].…”
Section: Introductionmentioning
confidence: 99%